2019
DOI: 10.26434/chemrxiv.6940379.v9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Master Key to the Problem of Reversible Chemical Hydrogen Storage is 12 kJ (mol H2)-1

Abstract: <p>This article outlines a potent theoretical formalism illuminating the boundaries to reversible solid hydrogen storage based on the ideal gas law and classic equilibrium thermodynamics. A global picture of chemical reversible hydrogen sorption is unveiled including a thermodynamic explanation of partial reversibility. This is utilized to elucidate a multitude of issues from metal hydride chemistry: Highlights are why the substitution of a mere 4 mol % Na by K in Ti-doped NaAlH<sub>4</sub> r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Advantageously simple in structure, it nonetheless offers a good approximation for hydrogen behaviour at typical metal hydride reaction conditions (T > 300 K, p < 100 bar). Since -H is equal to the excursion of the gas phase chemical potential from µ°, 7 it figures by amount to a pV m -energy term expressible via the ideal gas law which is shown in equation 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantageously simple in structure, it nonetheless offers a good approximation for hydrogen behaviour at typical metal hydride reaction conditions (T > 300 K, p < 100 bar). Since -H is equal to the excursion of the gas phase chemical potential from µ°, 7 it figures by amount to a pV m -energy term expressible via the ideal gas law which is shown in equation 2.…”
Section: Resultsmentioning
confidence: 99%
“…the density ); placing this gram-volume element in a hydrogen atmosphere at p° entails the formation of the metal hydride while the chemical potential of the gas phase changes by -H = µ H2 and pressure above the sorbent drops to a fraction x of p°. 7 In order to re-establish a pressure of p° above the sorbent, the temperature H/S = T 1bar is required. While the initial hydrogenation pressure p° drops to a fraction x, the metal volume expands by V and at the end of the absorption process, the chemical potentials of the gas and sorbent phase are on parity.…”
Section: Methodical Approachmentioning
confidence: 99%
“…It is reasonable to relate the effects caused by KH-doping with the next stable mixed alanate K 2 NaAlH 6 , 9 as KNa 2 AlH 6 is instable. 11,12 Its density is calculated by the entropy method, 10 on basis of the data of SØRBY et al, 13 as shown in equations 3a to 3c; the required NaH and Al densities base on Römpp's chemistry lexicon, 14,15 those of KH on data provided by American Elements.…”
Section: Resultsmentioning
confidence: 99%
“…That tells something of significance although nobody except the author seemingly ever attempted to make global sense out of that: the point about the equilibrium nature of reversible chemical hydrogen storage and doping effects has already been made from a gas phase perspective. 8,9 While that general solution comes in terms of hydrogen gas chemical potential, 8,9 i.e. temperature and pressure, switching perspective from gas to sorbent phase thermodynamics entails a change in metrics towards sorbent phase molar volume: That way the flipside manifestation of a chemical potential change in the gas phase shows in the equilibrium system.…”
Section: Introductionmentioning
confidence: 99%
“…On basis of equation 13, the conditional pressure for [AlH 4 ]-formation can be figured out as shown in equation 14a to 14c: the change in arithmetic sign due to the perspective switch from sorbent to gas phase between equations 14a and 14b is noteworthy, 7 leading to the result that for [AlH 4 ]-formation pressure needs to be larger than 78.53 bar ≈ 79 bar.…”
mentioning
confidence: 99%